Transforming Pesantren Management: Integrating Good Governance to Drive Institutional and Financial Independence: manajemen pendidikan islam - Juli Ahirin; Muhammad Istan; Irwan Fathurrochman; Jumira Warlizasusi (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyse the implementation of good governance principles in pesantren management in Bengkulu Province, to identify the supporting and inhibiting factors influencing its application, and to evaluate the extent to which such implementation contributes to the achievement of pesantren independence. The analysis emphasises three key dimensions of independence: financial, institutional, and academic. Through an in-depth qualitative inquiry, this research seeks to provide a comprehensive understanding of the relevance and strategic significance of good governance in strengthening the autonomy and sustainability of Islamic educational institutions in the region. A qualitative research approach was adopted to explore in detail the dynamics of implementing good governance principles and their implications for institutional independence. The study was conducted in several representative pesantren in Bengkulu Province, selected based on their scale (large, medium, and small) and organisational characteristics, particularly the presence of business units or managerial structures reflecting independent governance. The findings reveal that the implementation of good governance principles, transparency, accountability, participation, effectiveness and efficiency, independence, and fairness has shown notable progress, although the degree of application varies among institutions. Supporting factors include the charismatic leadership of the kiai, a strong culture of independence, competent human resources, community participation, alumni engagement, and supportive government policies. Conversely, inhibiting factors comprise limited financial capacity, weak managerial competence, resistance to change, and dependence on external assistance. Overall, the application of good governance contributes strategically to enhancing pesantren independence across financial, institutional, and academic dimensions through transparent fund management, professional governance, and curriculum innovation